THE EFFECTIVENESS OF THE ECOPRINT-BASED PANCASILA STUDENT PROFILE STRENGTHENING (P5) PROJECT IN DEVELOPING STUDENT CREATIVITY - Alpinah Damayanti; Imamudin, Imamudin; Munawaroh, Munawaroh (LPPM Universitas Bina Bangsa, 2026)
This study aims to determine the effectiveness of ecoprint-based P5 to develop the creativity of 5th grade students in economic activity material at SDN Banjarsari 02. This study is a quantitative study with a pre-experimental method using a one group pretest-posttest design. The population in this study was all 5B classes of SDN Banjasari 02, totaling 41 with a sample of only 30 students, data collection techniques used were questionnaires, tests and documentation, sampling techniques used were purposive sampling techniques. Based on the results of statistical analysis of students' creativity skills, the pretest average was 50.17 and the posttest result was 71.83 and an increase after treatment was carried out was as large as 21%, while the results of the normality test for the pretest value of 0.006 were said to be abnormal because they were at a value <0.05, while the posttest value was 0.090 which means the posttest value was said to be normal. The results of the hypothesis test show that the value obtained is significant 0.000 <0.05 which indicates that there is a significant difference between the initial and final variables, based on the results of the N gain test, showing the development of student creativity in the pre-experiment of 0.4393 including the moderate category, this category shows that the P5 ecoprint-based learning shows an increase and development of students' creativity skills which is quite effective.